MMAC/PTEN gene expression in endometrial cancer – RT-PCR studies - Sobczuk, Anna; Romanowicz-Makowska, Hanna; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2007)
Mutations in the MMAC/PTEN (phosphatase and tensin homologue deleted on chromosome 10) gene are documented in cancers of the breast, prostate, ovary, colon, melanoma, glioblastoma, lymphoma and endometrium. In the present work MMAC/PTEN gene expression in women with endometrial adenocarcinoma (n=70) in RNA samples obtained from cancer tissue were investigated. Control DNA was obtained from 68 normal endometrial tissue samples. The MMAC/PTEN expression was determined by RT-PCR analysis. Expression of the MMAC/PTEN gene in endometrial adenocarcinoma cases was significantly reduced compared to the expression in the normal samples (p<0.05). Furthermore a significant difference (p<0.05) was observed between the expression of MMAC/PTEN in stage III versus lower stages of endometrial cancer. The results support the hypothesis that MMAC/PTEN gene expression may be associated with the incidence of endometrial cancer.